Sovremennye Cojnye Meniteli I Kananeinjenernye Construction And Reconstruction Of Cojnyx Defects In The Maxillofacial Area (Texas Journal of Medical Science, 2026)
Restoration of the jaw defect in the maxillofacial region remains one of the most common types of reconstructive surgery due to the combination of high functional and aesthetic requirements. Traditional methods ( autodermoplasty , loskutnye operatsii) have a limited volume of donor tissue, risk of donor morbidity and expressed rubtsevaniem. Development of kojnyx zameniteley and tissue engineering construction (TIK) has opened up new possibilities for the regeneration of kojnyx cover skins, including the use of biopolymer matrices, cellular transplants, mesenchymal stem cells, and also technological 3Dbioprinting